Literature Review Potensi Fotokimia Sulforaphane Dalam Pengelolaan Pasien Hiperglikemia - Nirmala, Nema Tirta (SM Institute, 2025)
ABSTRACT Sulforaphane is a phytochemical compound found naturally in cruciferous vegetables such as broccoli, cabbage, and cauliflower. This compound has gained attention due to its potential in the prevention of chronic diseases. Sulforaphane exhibits various bioactive activities, including antioxidant, anti-inflammatory, and detoxifying effects. The mechanism of action of sulforaphane in disease prevention is believed to involve the induction of phase II detoxifying enzymes, modulation of cell signaling pathways, and inhibition of cancer cell growth. This study uses a journal review method based on data collection through inclusion and exclusion criteria obtained from the Google Scholar search engine, including national journals, textbooks, and scientific articles published after 2015. Keywords : Sulforaphane, Antioksidan